Positioning and integrity monitoring using the new DFMC SBAS service in the road transport - Wang, Kan; El-Mowafy, Ahmed (2020)
Australia and New Zealand has initiated a two-year test-bed in 2017 for the new generation of Satellite-Based Augmentation System (SBAS). In addition to the legacy L1 service, the test-bed broadcasts SBAS messages through L5 to support the dual-frequency multi-constellation (DFMC) service for GPS and Galileo. Furthermore, PPP corrections were also sent via L1 and L5 to support the PPP service for dual-frequency GPS users and GPS/Galileo users, respectively.